The Semiotics of Sadism in Putu Wijaya’s Nyali: A Todorov's Semiotic Perspective - Annisa Rahma Sari; Moh Atikurrahman (Universitas Indraprasta PGRI, 2022)
Literary work is an structure of expression built from a second level semiotic system (connotative). Literary language is distinctive and different from everyday language (denotative). Elements in literature emphasize communicative elements in the form of creativity and authenticity of pronunciation (narratology). To find out the meaning of literary texts, semiotics offers a systematic approach in studying the signs contained in a literary work. This study places Nyali, a Putu Wijaya’s novel as the object of study using Tvetan Todorov's semiotic approach. In marking schemes such as literary works, Todorov divides semiotic levels into syntax, semantics, and pragmatics. The results of the study concluded that in both aspects, namely the syntax contains prepositions and sequences; Semantics shows that there are two characters that become the common thread of character and character elements, namely Kropos and General Leonel. Kropos is stubborn, strange, consistent, firm and steadfast. On the other hand, General Leonel has an arrogant, shrewd, structured and decisive character.Keywords: Nyali, Putu Wijaya, semiotic, Todorov, G30S.